OP0008 Deficient autophagy induces chondrocyte dysfunction through lamin a/c accumulation in aging and osteoarthritis. (15th June 2017) - Figueroa, P Lόpez de; Nogueira-Recalde, U; Calamia, V; Osorio, FG; Lotz, M; Lόpez-Otín, C; Blanco, FJ; Carames, B
Abstract : Background: Aging-related Osteoarthritis (OA) is characterized by insufficient extracellular matrix synthesis and articular cartilage degradation. Autophagy is essential to maintain chondrocyte homeostasis by regulating the intracellular macromolecule and organelle turnover (1). Previous findings indicated that autophagy is defective in Aging and OA articular cartilage (2, 3). However, the specific target/-s that regulates this homeostatic mechanism and affect cartilage integrity are still unknown. Objectives: The objective of study is to identify targets regulating autophagy in human chondrocytes. Methods: We performed quantitative proteomic analysis of Atg5 knockdown primary uman chondrocytes using iTRAQ (isobaric tags for relative and absolute quantitation) labeling coupled with on-line 2D LC/MS/MS. Protein identification and quantification were performed using Protein Pilot Software v 4.0. Each MS/MS spectrum was searched in the Uniprot/Swissprot database for Homo sapiens . Human chondrocytes and human cartilage from healthy, aged and OA patients were employed to confirm the role of the identified target by Western Blot (WB), Inmunofluorescence (IF) and Inmunohistochemistry (IHC). Importanly, CRISPR/Cas9 genome editing technology was used for mechanism of action studies. Results: 24 out of 487 proteins were significantly altered (p<0.05) in response to defective autophagy. Cytoskeleton organization, collagen catabolism, oxidative stress, and aging pathways were affected. Interestingly, Lamin A/C, a nuclear protein implicated in cell senescence, was found upregulated under defective autophagy. Increased Lamin A/C expression was found in human chondrocytes with reduced autophagy. Furthermore, aged and OA human cartilage showed increased Lamin A/C expression. Induction of chondrocyte senescence by genetic deletion of Zinc Metalloproteinase STE24 (Zmpste24) via CRISPR-Cas9, lead to Lamin A/C accumulation, accompanied by a reduction of LC3 and increased chondrocyte death and mitochondrial dysfunction, suggesting that deficient autophagy is correlated with senescence of human articular cartilage. Conclusions: Lamin A/C, a nuclear protein contributing to structural integrity to the nucleus and matrix was identified as candidate target for regulating cartilage function under defective autophagy, such as aging and OA. These results support the hypothesis that autophagy is decreased with aging. Therefore, targeting Lamin A/C might be a promising strategy to find novel therapeutics for cartilage aging and OA. References: Lotz MK and Caramés B. Autophagy and cartilage homeostasis mechanisms in joint health, aging and OA. Nat Rev Rheumatol 2011;7:579–587. Caramés B, Olmer M, Kiosses WB, Lotz MK. The relationship of autophagy defects to cartilage damage during joint aging in a mouse model. Arthritis Rheumatol 2015;67:1568–76. Acknowledgements: This study was supported by Instituto de Salud Carlos III- Ministerio de Economía y Competitividad, Spain-CP11/00095 and Fondo Europeo de Desarrollo Regional (FEDER). Disclosure of Interest: None declared